Identifying light impurities in transition metal dichalcogenides: the local vibrational modes of S and O in ReSe2 and MoSe2. (December 2017) - Hart, Lewis; Webb, James; Murkin, Stephen; Wolverson, Daniel; Lin, Der-Yuh
Abstract The transition metal dichalcogenides provide a rich field for the study of two-dimensional materials, with metals, semiconductors, superconductors and charge density wave materials being known. Members of this family are typically hexagonal, but those based on rhenium (ReSe2 and ReS2 ) and their ternary alloys are attracting attention due to their triclinic structure and their resulting, strong in-plane anisotropy. Here, Raman spectra of dilute ReSe2  -  x Sx alloys containing low levels of sulfur (x  ≤ 0.25) were obtained in order to investigate the distribution of substitutional sulfur atoms over the non-equivalent chalcogen sites of the ReSe2 unit cell. Four different Raman bands arising from the local vibrational modes of sulfur atoms were observed, corresponding to these four sites. One local vibrational mode has a substantially in-plane displacement of the sulfur atom, two are partially out-of-plane and one is completely out-of-plane. The interpretation of the experimental data is based on calculations of the lattice dynamics and non-resonant Raman tensors of a model alloy via density functional theory. For comparison, polarization-dependent Raman spectra of pure ReS2 are also presented; a dramatic increase in the Raman cross-section is found for the out-of-plane modes when the excitation polarization is normal to the layers and the light propagates in the layer plane. A similar increase in cross-section is found experimentally for the local vibrational modes of sulfur in dilute ReSe2 -x  Sx alloys and is predicted for dilute sulfur-containing alloys based on MoSe2 . The analogous local vibrational modes of substitutional oxygen impurities in ReSe2 were also investigated computationally. Optical spectroscopy: vibrational fingerprints of impurities in ReSe2 and MoSe2 The Raman spectra of ReSe2-x Sx alloys allows investigation of the distribution of substitutional sulfur atoms within the lattice of ReSe2 . A team led by Lewis S. Hart at the University of Bath performed a combination of Raman spectroscopy at visible excitation wavelengths and density functional perturbation theory on ternary ReSe2-x Sx alloys obtained by chemical vapor transport. The combination of a traditional normal incidence configuration and an "edge-on" geometry allowed identification of in-plane and out-of-plane Raman features, optically active in the respective experiments owing to their specific selection rules. The frequencies of the observed local vibrational modes arising from sulfur and oxygen atoms were observed to change as a function of the stoichiometric composition of the alloy, thus providing a means of monitoring such impurities. A similar effect was predicted for MoSe2-x Sx alloys.